(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Determining the factors affecting the satisfaction and analyzing Alumni’s satisfaction on training activities at Hai Duong Cental Collegge of Pharmacy. Methods: A cross-sectional study was conducted on 282 regular college students of Course 10, Hai Duong Central College of Pharmacy who graduated in September 2020 (Alumni). Results: There are 4 factors affecting Alumni’s satisfaction with training activities at Hai Duong Central College of Pharmacy with statistical significance in order of influence: (1) Teaching staff, (2) Training program, (3) Facilities & career guidance activities and (4) Support process and activities. These 4 factors explain 68,5% of the variation Alumni’s satisfaction. In addition, the study also shows that the employment status is a factor that effects the Alumni’s satisfaction, the alumni group with a job that is suitable for the training major feels more satisfied than the alumni group without a job.